Frequência de colonização e bactérias isoladas de ponta de cateter de peridural implantado para analgesia pós-operatória - Stabille, Débora Miranda Diogo (2014)
Objectives: The considerable increase in the use of epidural analgesia with catheters leads to the need to establish the security of the method. Although infections have been constant targets of discussions in epidural analgesia, studies have been limited to case reports and retrospective reviews. The aim of this study was prospective and epidemiological analysis of patients admitted to medical wards undergoing epidural analgesia postoperatively, as well as the incidence of catheter colonization and bacteria responsible for these settlements. Methods: From November 2011 to April 2012 were assessed patients electively operated and maintained under analgesia by epidural catheter hospitalized in surgical wards in Hospital of the Federal University of Uberlândia. The tip of the catheter was collected for microbiological qualitative and semi-quantitative analysis. Results: Six (8.8%) of 68 catheter tips cultured had positive cultures. No patient had superficial or deep infection. The mean duration of catheter use was 43.45 hours (18-118 hours), 51.1 hours in colonized catheters and 42.7 hours among those who showed no colonization (P=0.0894). The type of surgery (contaminated or uncontaminated), physical status of patients and duration of surgery showed no relationship with the colonization of catheters. The isolated microorganisms in catheter tips were Staphylococcus aureus, Pseudomonas aeruginosa and Sphingomonas paucimobilis. Conclusion: It is concluded that the epidural catheter for analgesia postoperative, in conditions of this study, revealed procedure with low risk of bacterial colonization in patients from surgical wards.